Upaya Meningkatkan Kemampuan Menyimak Melalui Metode Bercerita pada Anak - Suhartini Nurul Azminah; Purbandari, Mimi; Citrasukmawati, Alfina (Jambura Early Childhood Education Journal, 2023)
Preliminary observations show that listening skills in group B of Citra Blessing Kindergarten have not yet developed optimally. The problem that arises is the way the teacher presents the story is less attractive and seems monotonous, so that students are less interested in listening to the contents of the reading. Based on these conditions, the research was carried out with the aim; 1) to find out the efforts to improve listening skills through the storytelling method for children; 2) to find out the increase in listening skills through the storytelling method for children. This study used classroom action research (PTK) which was carried out in two cycles. Data collection techniques using observation, interviews, and documentation with data analysis techniques using the percentage formula. The results showed that in the first cycle, there were 8 children who developed according to expectations (BSH) with a percentage of 44.44%, then it increased in cycle II to 94.44% with very good development criteria (BSB) there were 11 students or 61. 11% and developing according to expectations (BSH) there are 6 students at 33.33% percentage gain. This shows that presenting the right story can improve listening skills in children.